Controlling the setting times of one-part alkali-activated slag by using honeycomb ceramics as carrier of sodium silicate activator. (28th February 2020) - Liu, Cun; Yao, Xiao; Zhang, Wei
Highlights: Alkali activated slag cement (AASC) by porous material as carrier of the activator. The setting time of AASC is prolonged to more than 5 h. The compressive strength of this one-part AASC can reach over 40 MPa. The recycled honeycomb ceramics reflects the concept of green materials. Abstract: A solid alkali source is a great choice to make one-part alkali activated materials (AAM). Conventional slag-based AAM always suffer from short setting time and unsafe operation with liquid alkaline activators, thus restricting their usage in industry. This study aims to synthesize a new kind of one-part alkali-activated slag cement by using a porous honeycomb ceramic (HCC) as the carrier of sodium silicate activator. The solid activator was produced by making the honeycomb ceramic absorb water glass (Ms = 3.24, 8.21 wt% Na2 O, 25.8%wt SiO2 ), drying for 5 h at 125 °C and then grinding it to powder with particle sizes between 10 and 50 μm. In this study, the result indicates that setting time of alkali activated slag cement (AASC) was successfully extended to at least 5 h by using the solid activator. The maximum compressive strength of the specimens made with 5% NaOH + 40% HCC and 6% NaOH + 40% HCC was 40 MPa after 28 d of curing time. XRD (X-ray diffraction), FTIR (Fourier Transform infrared spectroscopy), SEM (Scanning Electron Microscope) and linear shrinkage analysis were applied in order to study the hydration product and the effect of the addition of HCC to the AASC. In terms of the strength properties and setting time, this one-part AASC could be classified as a Type 32.5 N and CEM IIIC class cement according to the European standard EN-197.